(untitled) (Palestine Issues on Indonesian Society, 2024)
This paper investigates the role of public opinion and grassroots movements in Indonesia’s foreign policy stance on Palestine. Over the years, Indonesian civil society—including political activists, religious groups, and youth organizations—has demonstrated significant solidarity with Palestine, influencing the country’s diplomatic position. The study analyzes the ways in which public opinion, particularly in the form of mass protests, petitions, and advocacy campaigns, has impacted Indonesia’s official policy towards Palestine. By examining key historical moments, such as Indonesia’s support in international forums, and the role of grassroots movements, this paper explores the intersection of public sentiment and state diplomacy. The study also highlights the unique position of Indonesia, a Muslim-majority country with strong anti-colonial roots, and how this background shapes its political engagement with Palestine. This paper argues that while government policies may shift, grassroots mobilization remains a constant force in ensuring that Palestine remains a central issue in Indonesia’s foreign policy discourse.